Biocontrol and Growth-promoting Potential of Native Trichoderma Isolate from Himalayan Foothills Against Tomato Fungal Pathogens - Bhardwaj, Swadha; Chandel, Sunita (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during August, 2022–March, 2023 in the northwestern region of the Himalayan foothills on isolating and profiling a new Trichoderma strain from Himalayan soils for its antagonistic and growth-promoting effects against tomato pathogenic fungi. Soil samples were collected from various locations were subjected to serial dilution to isolate Trichoderma. The culture was evaluated morphologically based on colony characteristics, spore shape, and hyphal structure under a microscope. The isolate’s DNA was extracted and amplified for genetic identification and profiling. In vitro and pot assays were conducted to determine antagonistic activity and plant growth-promoting effects against major tomato fungal pathogens. Morphological features revealed that isolate exhibited rapid colony growth characterized by cottony mycelium and green conidia, showing typical characteristics of genus Trichoderma. Molecular identification using ribosomal Deoxy-ribomucleic acid sequencing of the Internal Transcribed Spacer confirmed isolate’s taxonomic identity as Trichoderma sp. isolate SUB11780421PII. Laboratory tests in Petri plates showed that it inhibited pathogen growth by 33 mm resulted to 52.72% of mycelial inhibition. In pot culture trials, it reduced disease incidence by 20% for Sclerotium rolfsii. The reduction was 30% for Fusarium oxysporum f. sp. lycopersici, while a more pronounced disease suppression of 35% was observed against Rhizoctonia solani. Additionally, this novel isolate from the foothills of the Himalayas promoted root (3.08 cm) and shoot growth (12.39 cm). These outcomes suggested that Trichoderma sp. isolate SUB11780421PII showed strong potential as a biological organism for mitigating diseases and supporting resilient agriculture, marking its first report from the region.